Effects of access to credit on the performance of SMEs in the Congo - Fabrice-Gilles Ndombi Avouba (The Journal of Entrepreneurial Finance (JEF), 2022)
This paper proposes to analyze the effects of access to credit on the performance of SMEs in Congo. To this end, we used the theoretical model developed by Stiglitz and Weiss (1981). From an econometric point of view, we estimated a multiple linear regression model using the ordinary least square technique due to the absence of endogeneity. This application, as well as the statistical and econometric analyses that followed, were carried out using microeconomic data from the survey of very small, small, medium-sized enterprises and artisans in the Congo, which was carried out thanks to the multiple contributions of the managers of the National Institute of Statistics (INS). As a result, it was found that access to credit is neutral with respect to the performance of SMEs. This result led to an economic policy implication.
Keywords: 650; Credit; Performance; Congo; Multiple linear regression model